Developing-Economy preferences for imported organic food products. Issue 3 (27th May 2019) - Nuttavuthisit, Krittinee; Thøgersen, John
Abstract: Preference for imported products are often found in developing countries. A mixed method case study is employed to investigate why and when, using Thailand and organic food as the case. In-store interviews (N = 67), two focus groups (N = 16) and an online survey with consumers screened for knowledge of organic food (N = 965) are reported. A domestic country bias is revealed, but co-existing with a higher trust in the standards and certifications of developed countries. Hence, developed countries' credible institutions are a competitive advantage that allows them to compete with similar but cheaper products from developing countries.